Media construction of Enggano Island’s isolation: A comparative framing analysis of detikcom and Kompas.com using Entman’s model - Hasyim, Taufik; Kartika, Yeni; Sari, Rizza Armelvia (Privietlab, 2025)
This study explores how two leading national online media, detikcom and Kompas.com, construct news frames around the issue of isolation on Enggano Island through the analytical lens of Robert Entman’s framing model. Enggano, a frontier island in Bengkulu Province, has long been characterized by poor transport connectivity, limited infrastructure, and minimal state attention. Each media outlet offers a different interpretive stance, revealing how developmental inequality and the dynamics between Indonesia’s center and periphery are discursively shaped. This study adopts a qualitative framing analysis by applying Entman’s four analytical dimensions: defining the problem, diagnosing causes, making moral evaluations, and suggesting remedies. The data comprise ten online articles published in June 2025, all addressing isolation and development on Enggano. The findings indicate that detikcom constructs the issue primarily through geographical and factual perspectives, portraying Enggano as a remote area requiring infrastructure improvement. Conversely, Kompas.com situates the story within the broader context of policy disparity and governmental accountability, using a tone that is both critical and empathetic toward local communities. In terms of moral evaluation, detikcom maintains descriptive neutrality, while Kompas.com underscores unequal national development and advocates for implicit moral concern. Despite these differences, both outlets stop short of offering concrete policy recommendations. Overall, this study demonstrates that media framing serves as a pivotal mechanism for shaping how isolation and developmental inequality are perceived in Indonesia’s peripheral regions. The findings extend theoretical discussions in development communication and media studies, particularly regarding how the national media reproduces or challenges spatial inequalities within the discourse of public policy and national development.